Optimization of Predictive Policing Technology for Prevention of Brawling Crimes at Bekasi City Metro Police Station - Edco, Herman; Simbolon, Wijaya; Nita, Surya; Koto, Zulkarnein (Journal of Law, Politic and Humanities, 2025)
The phenomenon of brawl-related crime in the jurisdiction of the Bekasi City Metro Police, which has significantly increased since 2021, represents deviant behavior from social norms commonly referred to as juvenile delinquency. The objectives of this study are to analyze the effectiveness of the currently applied predictive policing technology in preventing brawl-related crime in the Bekasi City Metro Police jurisdiction, the challenges faced by the Bekasi City Metro Police in integrating predictive policing technology for preventing brawl-related crime, and optimal strategies for implementing predictive policing technology to improve the effectiveness of brawl prevention in the Bekasi City Metro Police jurisdiction. This study uses a qualitative research method. The theories used include predictive policing theory, evaluation theory, and SWOT theory. The results indicate that optimizing predictive policing technology at the Bekasi City Metro Police faces significant challenges related to ineffective data integration, limited technological infrastructure, and minimal training for police personnel. To improve its effectiveness, improvements are needed in data integration, adoption of advanced technologies such as big data and artificial intelligence, and intensive training for police personnel. Enhancing data quality, coordination between units, and active community involvement are also crucial to maximizing the technology’s capability in preventing brawls.